Performance consulting : applying performance improvement in human resource development - Rothwell, William J., 1951- (Jossey-Bass, 2014)
Improving individual and organizational performance is imperative to establishing and maintaining a high performance workplace, developing intellectual capital, promoting productivity, and enhancing profitability. Organizations must be flexible and agile in approaching business strategies. Against this backdrop, the time has come to revisit the role of training, HRD, and instructional design in today's organizations. Performance Consulting: Applying Performance Improvement in Human Resource Development is a leading-edge text that maps to existing curricula and syllabi, as well as real-world world.